Cultural distance and negotiation behavior : Perception of entrepreneurs operating in Turku - Kupri, Ana (My University, 2014)
This thesis investigates the influence of cultural distance on entrepreneurs’ negotiation behaviour. For this purpose, Turku was chosen as the unit of analysis due to the exponential demographic change experienced during the last two decades that has derived in a more diversified local environment. The research aim set for this study was to identify to what extent entrepreneurs face cultural distance, how cultural distance influences the entrepreneur’s negotiation behaviour and how can it be addressed in order to turn dissimilarities into opportunities. This study presented the relation and apparent dichotomy of cultural distance and global culture, including the component of diversity. The impact of cultural distance in the entrepreneurial mindset and its consequent effect in negotiation behaviour was presented too. Addressing questions about the way individuals perceive, behave and interact allowed the use of interviews for this qualitative research study. In the empirical part of this study it was found that negotiation behaviour differed in terms of how congenial entrepreneurs felt when managing cultural distance, encompassing their performance. It was also acknowledged that after time and effort, some of the personal traits were enhanced while others reduced, allowing for more flexibility and adaptation. Furthermore, depending on the level of trust and shared interests, entrepreneurs determined their attitudinal approach, being adaptive or reactive subject to situational aspects. Additionally, it was found that the acquisition of cultural savvy not necessarily conveyed to more creativity. This experiential learning capability led to the proposition of new ways of behaviour. Likewise, it was proposed that growing cultural intelligence bridge distances, reducing mistrusts and misunderstandings. The capability of building more collaborative relationships allows entrepreneurs to see cultural distance as a cultural perspective instead of as a threat. Therefore it was recommended to focus on proximity rather than distance to better identify and exploit untapped opportunities and better perform when negotiating in whichever cultural conditions.